Evaluation of the CNC® prosthetic system in recurrent breast cancer patients with chemotherapy-induced alopecia: a pilot study - Alessandra Petruzzi; Anna Maria Mancuso; Sara Alfieri; Antonella Esposito; Gabriele Infante; Rosalba Miceli; Stefano Ospitali; Carla Ida Ripamonti; Claudia Borreani (BMC, 2022)
Abstract Background Chemotherapy-induced alopecia (CIA), although generally reversible, is felt as extremely distressing by patients with breast cancer. A certified medical device (Capelli Naturali a Contatto®-CNC®) was produced to provide patients with a personalized scalp prosthesis, reproducing the patient's original hair, resistant to any type of everyday or sporting activity, and hairdressing. Aims The present study aimed to evaluate the impact of the CNC® device on the patient's perception of their body image, psychological wellbeing, satisfaction, strengths and weakness of the CNC® device. Method A pilot study was carried out on 21 patients affected by CIA due to recurrent breast cancer. A mixed quantitative/qualitative method was used, including administering a questionnaire and a focus group. Results Based on the Body Image Scale, body image perception improved after 3 and 6 months using the device in the 20 patients who answered the questionnaire. No significant change over time emerged for the six dimensions investigated by the Italian version of the Psychological Well-Being Scale. The thematic analysis of the focus groups showed six themes: definition of the prosthetic device, acceptance of the proposal, experience with the conventional wig, strengths, weaknesses, economic issues. Conclusion Compared to the previous experience of CIA and the standard wig, the use of the CNC® device improved everyday life and may be proposed to women undergoing chemotherapy and expecting alopecia to prevent discomfort, social embarrassment, and compromised body image.